Microbiological and Chemical Characteristics of Smoked Tuna - Meigy Nelce Mailoa; Edir Lokollo; Dessyre Marlen Nendissa; Pavita Indriani Harsono (Jurnal Pengolahan Hasil Perikanan Indonesia, 2019)
Smoked fish is traditionally processed by fish through an open process of hot smoked. Smoked fish process in Indonesia, especially in Maluku, is still carried out traditionally with capital and small business scale so that the use of tools is still simple, besides the sanitation and hygiene of handling and processing are still low. The raw material used in this study is smoke tuna loin produced by Dusun Air Manis,Laha village. This study aims to determine the microbiological and chemical quality of the smoked fish that was produced from Dusun Air Manis, Laha village. The test parameters carried out consisted of microbiological tests: 1) Total microbes on frozen tuna loin, washing water, immersion water, bamboo, smoked racks and smoked tuna, 2) Escherichia coli test on frozen tuna loin, washing water, soaking water, smoked tuna, 3) Salmonella test on smoked tuna. Chemical analysis of smoked tuna included moisture and pH. The results showed that the total plate count (TPC), Escherichia coli and Salmonella on tuna loin smoke still met microbiological standards according to SNI 2725: 2013. Moisture of smoked tuna was 59% and still meets the quality standard according to SNI 2725: 2013 which is a maximum of 60%. The pH of smoked tuna was 5.8.